ANALYSIS OF HEAVY EQUIPMENT USAGE FOR INLET CONDUIT WORK ON CIJUREY DAM PROJECT PACKAGE 1 - Ega Dwi Prasetyo; Ekodjati Tunggulgeni; Anasya Arsita Laksmi (Universitas Udayana, 2024)
Earth excavation work cannot be separated from the use of heavy equipment, where job performance is expected to be completed in a fast time at a minimum cost. Thus, it is necessary to calculate tool productivity to determine the combination of heavy equipment usage in a job. The productivity of heavy equipment can be determined based on the cycle time of working tools, where the cycle time of each tool has a difference depending on the size of the tool and the type of material being worked on. The method used by comparing productivity between heavy equipment is calculated by observing the cycle time of heavy equipment in completing the work. The productivity comparison obtained is used to calculate the most efficient tool requirements in a job which then calculates the costs that need to be incurred to complete a job. In this case, the efficiency of the combination of heavy equipment fleets can be done if the productivity between tools is far enough adrift. This efficiency value can affect the length of working time or equipment costs, or both. In this study, the efficiency of heavy equipment in the earth excavation work of the Cijurey Dam inlet area can be done through changes in the combination of heavy equipment fleets which originally used two excavators and four dump trucks to three excavators and four dump trucks. The results of heavy equipment efficiency show an acceleration of work time and a reduction in cost expenditure, the new fleet change of heavy equipment is using fleet 3 which can streamline time up to 80 working hours and reduces costs by Rp97,543,226.67.